Taxonomic revision of the genus Plantago L. (Plantaginaceae) in Chile - Murillo G., Vielka E. (Scientia, 2012)
In this paper a taxonomic revision of the Chilean species of the genus Plantago L. is presented as well as a phenetic analysis on the basis of morphological features, which enables to infer grouping and sorting among species, establishing a 23 taxa for Chile. Of the main features that enable to separate the Plantago species are: the arrangement of leaves in the stem, where there is a group of species that shows leaves in the basal rosette without forming dense lawns, flowers in spikes, lanceolate or ovate leaves, obtuse apex, two or three seeds in the fruit, flat-convex seeds with foveolate testa. This occurs in the Virginica section of Plantago for Chile; while in the Oliganthos section, the plants form dense lawns, with single or pauciflora flowers forming a small bracteate head, linear leaves with acuminate apex which can be clear or green, one to eleven seeds in the fruit, concave-convex seeds with rugose testa. The Gnaphalioides section groups annual and perennial herbs with leaves in the basal rosette without forming dense lawns, flowers in spikes, linear leaves, two seeds in the fruit, concave-convex seeds with smooth testa, bright or dull. The genus Plantago is distributed worldwide except in the Antarctic and tropical plains, occupying sandy and rocky regions, humid places close to ravines, streams, 75 swamps, beach borders generally associated to water bodies. The altitudinal range of the species of the genus in Chile is quite varied, from sea level to 4,450m high. A key is provided to separate the species and for each one of them their synonymy, morphological description, geographical distribution, and comments on the habitat are given. Each species is attached their corresponding herbarium material studied. Se hace una revisión taxonómica de las especies chilenas del género Plantago L. y sobre la base de caracteres morfológicos, un análisis fenético, que permite hacer inferencias de agrupamiento y ordenación entre las especies, reconociendo 23 taxa para Chile. Dentro de los principales caracteres que permiten separar las especies de Plantago están: la disposición de las hojas en el tallo, donde se encuentra un grupo de especies que presentan hojas en roseta basal sin formar densos céspedes, flores en espigas, hojas lanceoladas u ovadas, ápice obtuso, dos o tres semillas en el fruto, semillas planoconvexas con testa foveolada, esto ocurre en la sección Virginica de Plantago para Chile, mientras que en la sección Oliganthos las plantas forman densos céspedes, con flores solitarias o pauciflora formando una pequeña cabezuela bracteada, hojas lineares con el ápice acuminado, el mismo puede ser transparente o verde, una a once semillas en el fruto, semillas cóncavo-convexas con testa rugosa. La sección Gnaphalioides agrupa hierbas anuales y perennes con hojas en roseta basal sin formar densos céspedes, flores en espigas, hojas lineares, dos semillas en el fruto, semillas cóncavo-convexas con testa lisa, brillante u opaca. El género Plantago está distribuido en todo el mundo con excepción del continente Antártico y las llanuras tropicales, ocupando regiones arenosas, rocosas, lugares húmedos, cercanos a quebradas, arroyos, vegas, bordes de playas generalmente asociadas a cuerpos de agua. El rango altitudinal de las especies del género en Chile es muy variable, desde el nivel del mar hasta los 4450 m de altitud. Se confecciona una clave para separar las especies y para cada una se entrega su sinonímia, descripción de su morfología, información sobre la distribución geográfica, comentarios sobre el hábitat. Cada especie va acompañada de su correspondiente material de herbario estudiado.